Young people, employment and work psychology : interventions and solutions - Carter, Angela J. (Routledge, 2019)
Youth unemployment and underemployment is a serious issue in most developed countries in the world. Having few young people in the workplace has serious and lasting consequences for generations of young people, their families, businesses and society as a whole. Dr Carter explores these important issues from multiple (and international) perspectives, offering research evidence and guiding frameworks from social and work psychology, to get more young people into good work. Young People, Employment and Work Psychology brings together educators, researchers, occupational psychologists, and government agencies responding to young people struggling to gain and sustain employment. Theoretically based and evidence-driven, this book explores the consequences of unemployment, suggests ways in which businesses can enable young people's first steps into employment and gives practical advice to young people and employers to prepare for and gain entry-level roles and develop more diverse workplaces. From the reasons why organizations are often reluctant to employ young people, to issues of motivation and confidence which often affect young people's perspective in looking for work, the book covers several interventions within both the public and private sector. This book is an invaluable resource for employers, policy makers and professionals working with young people, as well as students and researchers in work andorganizational psychology, HRM, business management and social policy. - Resumé vydavatel